Pediatric patients with attention deficit and hyperactivity disorder and accidental injuries: a cohort study - Ferrão, Tomás; Bravo, Mariana; Ministro, Diogo; Zenha, Raquel; Rebimbas, Sandra (International Journal of Contemporary Pediatrics, 2026)
Background: Attention deficit and hyperactivity disorder (ADHD) is linked to a higher risk of injuries, especially in childhood and adolescence. This study compares emergency department (ED) visits between pediatric patients with ADHD and healthy controls, identifying potential risk factors and differences in injury severity. Methods: Retrospective cohort study including patients diagnosed with ADHD at a Neurodevelopment Clinic, and a control group of patients born at the same hospital. Medical records were reviewed for clinical data (number of ED accidents since birth and severity outcomes such as splints, hospitalization, surgeries, inter-hospital transfers and sequelae). Parametric measurements were used due to the sample size and absence of skewness. Negative binomial regression accounted for overdispersion in incidence rates. Results: We analyzed 316 ADHD cases and 316 controls. Mean age was 11.9 years (SD 2.4), similar to controls (p=0.998), with 66.5% males in both groups. ADHD patients had 537 unintentional injury ED visits (controls: 387), an incidence rate ratio (IRR) of 1.36 (95% CI: 1.11-1.67). The IRR was higher for episodes ≥6 years (IRR 1.48; 95% CI: 1.16-1.88). Severity outcomes were similar (p=0.257). Lower parental education was associated with more episodes (IRR 1.39; 95% CI: 0.989-1.96). Comorbidities did not affect injury incidence (p=0.425), but patients without comorbidities required more procedures and transfers (p=0.018 and p=0.013, respectively). 79.7% of cases had most/all ED visits before starting psychostimulants. Conclusions: Our study supports the increased risk of injuries among pediatric ADHD patients. While injury severity was comparable to controls, ADHD patients without comorbidities had greater severity. Psychostimulants suggested a protective effect.